Financial globalization and monetary policy - Michael B. Devereux; Alan Sutherland (Deutsche Bundesbank, 2008)
Recent data show substantial increases in the size of gross external asset and liability positions. The implications of these developments for optimal conduct of monetary policy are analyzed in a standard open economy model which is augmented to allow for endogenous portfolio choice. The model shows that monetary policy takes on new importance due to its impact on nominal asset returns. Nevertheless, the case for price stability as an optimal monetary rule remains. In fact, it is reinforced. Even without nominal price rigidities, price stability is optimal because it enhances the risk sharing properties of nominal bonds.
Keywords: F41; E58; E52; 330; Portfolio Choice; International Risk Sharing; Exchange Rate; Internationaler Finanzmarkt; Rentenmarkt; Portfolio-Management; Investitionsrisiko; Geldpolitik; Preisniveaustabilität; Theorie